Factors affecting arteriovenous fistula dysfunction: A narrative review. Issue 2 (March 2020) - Gameiro, Joana; Ibeas, Jose
Vascular access dysfunction is one of the most important causes of morbidity and mortality in haemodialysis patients, contributing to up to one third of hospitalisations and accounting for a significant amount of the health care costs of these patients. In the past decades, significant scientific advances in understanding mechanisms of arteriovenous fistula maturation and failure have contributed to an increase in the amount of research into techniques for creation and strategies for arteriovenous fistula dysfunction prevention and treatment, in order to improve patient care and outcomes. The aim of this review is to describe the pathogenesis of vascular access failure and provide a comprehensive analysis of the associated risk factors and causes of vascular access failure, in order to interpret possible future therapeutic approaches. Arteriovenous fistula failure is a multifactorial process resulting from the combination of upstream and downstream events with consequent venous neo-intimal hyperplasia and/or inadequate outward remodelling. Inflammation appears to be central in the biology of arteriovenous fistula dysfunction but important triggers still need to be revealed. Given the significant association of arteriovenous fistula failure and patient's prognosis, it is therefore imperative to further research in this area in order to improve prevention, surveillance and treatment, and ultimately patient care and outcomes.